2019
DOI: 10.1002/brb3.1445
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in thalamic connectivity following stress and its association with future depression severity

Abstract: IntroductionTracking stress‐induced brain activity and connectivity dynamically and examining activity/connectivity‐associated recovery ability after stress might be an effective way of detecting stress vulnerability.MethodsUsing two widely used stress paradigms, a speech task (social stress) and a mathematical calculation task (mental loading stress), we examined common changes in regional homogeneity (ReHo) and functional connectivity (FC) before, during, and after the two stressful tasks in thirty‐nine coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…The patient with a mildly significant decrease in perfusion in the bilateral thalamus and bilateral cerebellum on the 15 O-water PET did not show any abnormalities on their MRI perfusion image, which may indicate minor perfusion changes or nonspecific findings, although thalamus connectome data have suggested an association with anxiety. 15 , 16 However, the diffuse increase in perfusion in the cerebral white matter was observed on both the 15 O-water PET and MRI perfusion images. Previous studies have shown that increased cerebral blood volume and CBF can be detected in normal-appearing white matter in patients with inflammatory conditions, such as multiple sclerosis.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The patient with a mildly significant decrease in perfusion in the bilateral thalamus and bilateral cerebellum on the 15 O-water PET did not show any abnormalities on their MRI perfusion image, which may indicate minor perfusion changes or nonspecific findings, although thalamus connectome data have suggested an association with anxiety. 15 , 16 However, the diffuse increase in perfusion in the cerebral white matter was observed on both the 15 O-water PET and MRI perfusion images. Previous studies have shown that increased cerebral blood volume and CBF can be detected in normal-appearing white matter in patients with inflammatory conditions, such as multiple sclerosis.…”
Section: Discussionmentioning
confidence: 95%
“…Symptoms experienced may include vasovagal reactions and dissociative FIGURE 2. 15 O-water and cluster subtraction (P = 0.05) images of patients with neurological symptoms for the first visit and follow-up using the MIM software. Mildly significant decreased perfusion in the bilateral thalamus (A) and bilateral cerebellum (B) in patient 6 (C, D) Mildly diffuse increased perfusion in the cerebral white matter of patient 8 was also noted on both the 15 O-water and MRI perfusion images.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research shows that there are many interrupted network connectivity in MDD core network, such as default mode network, and the limbic system and so on. 9 , 10 The analysis of functional connectivity (FC) is based on seed points and relies on a priori hypothesis. The changes of voxel activity over time (such as regional homogeneity [ReHo] and low‐frequency fluctuation amplitude [ALFF]) can help to reveal the changes of cerebral blood flow in patients with stress‐induced MDD.…”
Section: Introductionmentioning
confidence: 99%